Implementation and use of digital solutions in printing production - Ivaskiv, R. (ТОВ «Видавництво Ліра-К», 2025)
This paper examines general approaches to the implementation of digital technologies in printing production, with a particular focus on the role of enterprise resource planning (ERP) systems in transforming business processes. It provides a brief analysis of the potential of digital solutions to optimize production and management workflows and outlines the key challenges associated with digitalization in the printing industry. The importance of a strategic approach to the integration of information systems in this field is emphasized.
Keywords: digital solutions; printing production